PENINGKATAN KEMAMPUAN MEMBACA AL-QUR’ANMENGGUNAKAN METODE IQRA’ MELALUI KEGIATAN (KKL) DI KECAMATAN NANGA TAYAP KABUPATEN KETAPANG - Mutmainnah Mutmainnah; Sahdan, Mujib, Dio Sahnannur, Eki Septiwuni, Fitri Indah Sari, Hamzah Haz (JOURNAL OF COMMUNITY DEDICATION, 2023)
This study aims to improve the ability to read the Qur'an using the Iqra' method through Field Work Lectures (KKL) in Nanga Tayap District, Ketapang Regency. The Iqra' method was chosen because of its effectiveness in helping participants learn to read the Qur'an gradually and systematically. The implementation of the activity involved students as facilitators who guided participants directly with an interactive approach and group learning. The evaluation results showed that 85% of participants experienced an increase in their ability to read the Qur'an, with active participant participation reaching 90%. The involvement of student facilitators was also high, at 95%, and 80% of the community showed an increase in awareness of the importance of religious education. The obstacles faced in the form of limited time and facilities can be overcome with flexible learning methods. In conclusion, the implementation of the Iqra' method through KKL is effective in improving the ability to read the Qur'an and has a positive impact on the community of Nanga Tayap District.